English-Filipino, Filipino-English legal dictionary an accompaniment to the labor code - Nalica, Christian Robert B. (2014)
This study entitled "English-Filipino, Filipino-English Legal Dictionary: An Accompaniment to the Labor Code" attempts to create a legal dictionary based on the Labor Code of the Philippines (PD 442). Major objectives were: to gather translated labor terms from English to Filipino, to re-rank reference materials that can give better and more accurate translation and to check which translated terms are acceptable technically Two major steps were used for the study: 1) Collection of terms and 2) Interviewing informants. Phase one involved literature scanning and translating using dictionaries and developed guidelines Phase two involved interviewing and getting advice from legal experts who were speakers of Filipino. The researcher solicited the assistance of six informants in validating the legal terms to Filipino. Of the six, four were legal practitioners while the other two were law student - all first speakers Filipino. After developing criteria for selecting terms in the Labor Code, a total of 390 terms were selected. Of the 390 terms, 277 have Filipino translations. On the other hand, 13 have no equivalent translations. The study concluded the following: 1) Mastery in a particular language was not enough for a valid translation. 2) Knowledge in the field was a major factor. 3) Collaboration with experts was very important. It also agreed to the previous researchers that legal translation should be matapat with the source language.